Dynamics of High School Certificate Examinations Demand: A Case Study of Kurdistan Region, Iraq - David Wafula Waswa; Mowafaq Muhammed Al-Kassab; Azhar Abdulrazak Alhasoo (Eurasian Journal of Science and Engineering, 2021)
College majors for high school students are mostly predicted by Grade Point Average (GPA) scores and standardized tests. Both predictors are applied by the regional government of Kurdistan, Iraq. The objectives of this research were to characterize dynamics that determine performance of high school students, in terms of both the standardized Wzary test and overall high school GPA, and the influence on their subsequent selection of college majors. Whether students who choose the same major could be assumed to have the similar cognitive abilities, on average, was also investigated by this paper. Data was collected via a questionnaire that was distributed to university students. The questionnaire sought to collect information on the academic performance in high school, socioeconomic status at the time, and parents’ education status. It was established that biology major students had a distinct higher GPA compared to other departments in the faculty of Education, and through multiple linear regression, it was established that mother’s education level, mode of transport to school, place of residence, and student’s age are some of the predictors of high school GPA.